2022
DOI: 10.9734/ajeba/2022/v22i2330741
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Literacy and Financial Inclusion on the Performance of MSME in Bogor City

Abstract: Aims: This study aims to analyze the impact of financial literacy and inclusion on the performance of MSMEs in the Bogor city region. The existence of MSMEs in Bogor city has an essential role that needs to analyze through financial literacy and inclusion approaches. Methodology: The respondents were selected through a non-probability sampling technique, mainly purposive sampling. Primary data was gathered by using a self-administered questionnaire with five points Likert scale. Multiple regression was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…),Mindra & Moya (2017),Bongomin et al (2016),Saputra & Dewi (2017),Hutabarat (2018), and Pulungan & Ndruru (2019), provide support for the findings of this study. According to Simanjuntak (2019), financial technology and financial literacy have a big impact on how financially included students are in North Sumatra.…”
supporting
confidence: 78%
“…),Mindra & Moya (2017),Bongomin et al (2016),Saputra & Dewi (2017),Hutabarat (2018), and Pulungan & Ndruru (2019), provide support for the findings of this study. According to Simanjuntak (2019), financial technology and financial literacy have a big impact on how financially included students are in North Sumatra.…”
supporting
confidence: 78%
“…Fintech, especially Shariah-based solutions, has been identified as a means to extend financial inclusion to MSMEs, addressing the capital challenges they often face (Budiman et al, 2024;Yuneline, 2022). Research has also shown that financial literacy and inclusion positively impact the performance of MSMEs, with fintech playing a role in facilitating effective product usage and skill development tailored to their needs (Puspitasari & Astrini, 2022). In conclusion, the integration of fintech in MSME financial management can lead to improved financial literacy, inclusive financial practices, and ultimately enhance the overall performance and sustainability of MSMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existence of MSMEs that are not maximized in their management is a problem that needs to be addressed [10]- [14]. The problem with almost all micro, small, and medium enterprises that cannot grow is due to the lack of capital they have, and the need for additional funds from outside parties in the form of assistance from the government or credit loans from financial institutions.The problem with almost all micro, small and medium enterprises that cannot develop is due to the lack of capital they have, and the need for additional funding from external parties, whether in the form of assistance from the government or loans from financial institutions..…”
Section: Introductionmentioning
confidence: 99%